Expression Profiles and DNA-Binding Affinity of Five ERF Genes in Bunches of Vitis vinifera cv. Cardinal Treated with High Levels of CO2 at Low Temperature - Romero, Irene; Vazquez-Hernandez, Maria; Escribano, M. I.; Merodio, Carmen; Sanchez-Ballesta, M. T. (Frontiers in Plant Science, 2016)
Ethylene response factors (ERFs) play an important role in plants by regulating defense response through interaction with various stress pathways. After harvest, table grapes (Vitis vinifera L.) are subject to a range of problems associated with postharvest storage at 0ºC, such as fungal attack, water loss and rachis browning. The application of a 3-day high CO2 treatment maintained fruit quality and activated the induction of transcription factors belonging to different families such as ERF. In this paper, we have isolated five VviERFs from table grapes cv. Cardinal, whose deduced amino acid sequence contained the conserved apetalous (AP2)/ERF domain. The phylogeny and putative conserved motifs in VviERFs were analyzed and compared with those previously reported in Vitis. VviERFs-c gene expression was studied by quantitative real-time RT-PCR (RT-qPCR) in the different tissues of bunches stored at low temperature and treated with high levels of CO2. The results showed that in most of the tissues analyzed, VviERFs-c gene expression was induced by the storage under normal atmosphere although the application of high levels of CO2 caused a greater increase in the VviERFs-c transcript accumulation. The promoter regions of two PRs (Pathogenesis Related Proteins), Vcchit1b and Vcgns1, were obtained and the in silico analysis revealed the presence of a cis-acting ethylene response element (GCC box). In addition, gene expression of these two PRs was analyzed in the pulp and rachis of CO2-treated and non-treated table grapes stored at 0ºC and results showed significant correlations with VviERF2-c and VviERF6L7-c gene expression in rachis, and between VviERF11-c and Vcchit1b in pulp. Finally by using electro mobility shift assays (EMSA), we denoted differences in binding of VviERFs to the GCC sequences present in the promoters of both PRs, with VviERF6L7-c being the only member which did not bind to any tested probe. Overall, our results suggest that the beneficial effect of high CO2 treatment maintaining table grape quality seems to be mediated by the regulation of ERFs and in particular VviERF2-c might play an important role by modulating the expression of PRs.